Closed loop operation of time-based accelerometers - Dias, Rosana A. (2012)
In this paper we present a method for closed-loop operation of pull-in time accelerometers. Accelerometers based on the measurement of the pull-in time of movable parallel-plates MEMS structures have already demonstrated very good resolution capabilities, with low requirements on the capacitive readout. However, open-loop operation delivers very low dynamic range and highly non-linear response. The closed-loop approach relies on electrostatic feedback using counter-actuation electrodes opposite to the pull-in direction and although the control algorithm used was very simple, the dynamic range has been effectively extended and the linearity improved.